Relationship between Use of Food Delivery Applications, Fat Intake, Physical Activity and Weight Status among Students - Sony, Aurelia Gracia Chiquita; Ilmi, Ibnu Malkan Bakhrul; Sofianita, Nur Intania; Octaria, Yessi Crosita (Jurnal Gizi dan Pangan, 2024)
This study aimed to determine the relationship between food delivery app usage, fat intake, physical activity, and the overweight status of students at public high school in Jakarta. The cross-sectional study involved 77 students from grades X and XI. The frequency of food delivery was grouped into ≥3 times/week or less. Types of food were grouped into light or heavy meals. Physical activity was measured using IPAQ-SF (International Physical Activity Questionnaire - Short Form) and fat intake using SQ FFQ (Semi-Quantitative - Food Frequency Questionnaire). Fat intake was grouped into sufficient and excess category. Physical activity was grouped into low and sufficient category. Chi-square analysis found that there is a significant correlation between overweight status and frequency of food delivery application usage (p<0.001). However, there is no significant correlation between overweight status with the type of food ordered (p=0.467) as well as the amount of food ordered (p=0.655). On the other hand, fat intake showed a significant association with overweight status in adolescents (p<0.001). A significant association was also found between physical activity and overweight (p<0.05). This study showed that the adolescents’ use of food delivery applications, fat intake, and physical activity have a significant correlation with their overweight status. However, the type and amount of food ordered did not show a significant correlation. Despite the insight offered, the study was small and limited in one school hence generalization of findings is limited. Thus, a larger study with diverse subjects is needed.